Withdrawal of sodium monensin when associated with virginiamycin during adaptation and finishing periods on feedlot performance, feeding behavior, carcass, rumen, and cecum morphometrics characteristics of Nellore cattle - Rigueiro, André L. N.; Pereira, Murilo C. S.; Silvestre, Antonio M.; Pinto, Ana Carolina J.; Felizari, Luana D.; Dias, Evandro F. F.; Demartini, Breno L.; Estevam, Daniela D.; Dellaqua, João V. T.; Souza, Katia L. R.; Silva, Leandro A. F.; Nunes, Ana B. P. C.; et al. (Frontiers in Veterinary Science, 2023)
This study aimed to evaluate the effects of withdrawal of monensin (MON) when associated with virginiamycin (VM) during the adaptation and finishing periods on feedlot performance of Nellore cattle. The experiment was designed as a completely randomized block replicated six times (four animals/pen) in which 120 Nellore bulls (378.4 ± 24.4 kg) were allocated in 30 pens and fed for 112 days according to the following treatments: (T1) MON during the entire feeding period; (T2) VM during the entire feeding period; (T3) MON+VM during the adaptation period and only VM during the finishing period 1 and 2; (T4) MON+VM during the entire feeding period; (T5) MON+VM during the adaptation and finishing period 1 and only VM during the finishing period 2. After 112 days on feed, no treatment effect was observed for DMI (P ≥ 0.12). However, bulls fed T5 had greater (P = 0.05) final BW and ADG when compared to T1, T2, and T4. Cattle from T3 and T5 groups presented heavier HCW (P = 0.05) than that fed T1, T2, and T4. Nellore bulls fed T1 and T5 had lower (P < 0.01) DMI variation than those receiving T2. The withdrawal of MON when associated with VM during the final third of the feedlot period improved overall final BW, ADG, and HCW when compared to bulls fed either MON or VM, but did not positively impact feedlot performance when compared to cattle that had MON withdrawn at the end of the adaptation period.